Effect of coating concentration on gas separation performance of polysulfone mixed matrix membrane for biomethane recovery from wastewater - N. N. Niam; S.M. Anisuzzaman; Chiam, Chel Ken; Murni Sundang; Rachel Fran Mansa; A. R. Razali; Noor Maizura Ismail (Penerbit UTM Press, 2025)
Anaerobic membrane bioreactor (AnMBR) provides a range of benefits which include high performance in extracting organic matter and energy production in the form of biogas. In this study, performance of mixed matrix membrane (MMM) to recover biomethane from wastewater was studied. Polymer matrix of polysulfone (Psf) incorporated with different inorganic fillers, halloysite nanotubes (HNT) and activated carbon (AC). Different concentration (3%, 4% and 5%) of MMM’s polydimethylsiloxane (PDMS) coating were examined by using scanning electron microscopy (SEM-EDX) and gas permeation tests. The morphological structures as well as permeability and selectivity of MMM towards carbon dioxide (CO₂) and methane (CH₄) were investigated. SEM analysis showed that increasing the concentration increases the thickness of the coated surface of the membrane. For MMMs-HNT, the thickness of the top layer increased 29.1% from the uncoated membrane to the highest concentration of PDMS coating while MMMs-AC showed the thickness of the membrane increased by 64.7%. The EDX results showed that there is 46% increase and 9.63% increased of silicon composition for both MMMs-HNT and MMMs-AC. For the gas separation performance, PDMS coated MMMs showed lower permeability but higher selectivity than uncoated MMMs. The highest selectivity of the membrane can be observed in 3wt% PDMS coated MMMs-HNT which is 15.83 with CO₂ and CH₄ permeance of 0.76 and 0.05 GPU, respectively.